O lugar do ensino de Geografia nos cursos de Pedagogia na modalidade a distância: possibilidades e desafios - Araújo, Sarah Mendonça de (2013)
From an historical point of view, the teaching of Geography has been a field with many transformations and disturbances. For many years, the traditional approach has shaped the teaching of Geography, basing itself on memorization and noncritical contact with reality. Accepting the importance of this subject for preparing students for citizenship and considering the great expansion of distance learning in our country, mainly for teacher education, our research was directed towards identifying how subject matters that explore the teaching of Geography have been proposed in pedagogical projects for Pedagogy majors in public institutions in Brazil, mainly in the southern, southwestern and center-and-western regions of Brazil. This work analyzes documents pertinent to twenty one pedagogical projects permitting to conclude that the curricular proposals for Geography subjects in Pedagogy undergraduate courses are a long way from expressing a consensual outline or similar perspectives in the studied universities. Among other points, we outline that important aspects of the distance learning scenario are still to be detailed and planned in the pedagogical projects of these undergraduate courses. We also make evident a relevant diversity in the proposition of subject matter Geography in these courses projects and the prominence in the syllabus of themes and subjects that specifically include topics related to the teaching of Geography instead of investigative aspects and contents pertaining to Geography itself.